Curcumin is a Potential Adjuvant to Alleviates Diabetic Retinal Injury via Reducing Oxidative Stress and Maintaining Nrf2 Pathway Homeostasis - Xie, Ting; Chen, Xiaodong; Chen, Wenyi; Huang, Sien; Peng, Xinye; Tian, Lingmei; Wu, Xuejie; Huang, Yan (Frontiers in Pharmacology, 2021)
Curcumin is a natural polyphenol compound with anti-diabetic, anti-oxidative, and anti-inflammatory effects. Although many studies have reported the protective effect of curcumin in diabetes mellitus or diabetic nephropathy, there is a lack of research on curcumin in diabetic retinopathy. The purpose of this study was to investigate the therapeutic effects of curcumin on the diabetic retinal injury. Streptozotocin (STZ)-induced diabetic rats (60, n =12 each) were respectively given curcumin orally (200 mg/kg/day), insulin subcutaneously (4-6 IU/ day), and combined therapy with curcumin and insulin for four weeks. Retinal histopathological changes, oxidative stress markers, and transcriptome profiles from each group were observed. Curcumin, insulin, or combination therapy significantly reduced blood glucose, alleviated oxidative stress, and improved pathological damage in diabetic rats. Curcumin not only significantly reduced retinal edema but also had a better anti-photoreceptor apoptosis effect than insulin. In the early stage of diabetes, the enhancement of oxidative stress in the retina induced the adaptive activation of the nuclear factor E2-associated factor 2 (Nrf2) pathway. Treatment of curcumin alleviated the compensatory activation of the Nrf2 pathway induced by oxidative stress, by virtue of its antioxidant ability to transfer hydrogen atoms to free radicals. When curcumin combined with insulin, the effect of maintaining Nrf2 pathway homeostasis in diabetic rats was better than that of insulin alone. Transcriptomic analyses revealed that curcumin either alone, or combined with insulin, inhibited the AGE-RAGE signaling pathway and the extracellular matrix (ECM)-receptor interaction in the diabetic retina. Thus, at the early stage of diabetes, curcumin can be used to alleviate diabetic retinal injury through its anti-oxidative effect. If taking curcumin as a potential complementary therapeutic option in combination with antihyperglycemic agents, which would lead to more effective therapeutic outcomes against diabetic complications.